The impact of orphan histidine kinases and phosphotransfer proteins on the regulation of clostridial sporulation initiation - Iman Mehdizadeh Gohari; Adrianne N. Edwards; Shonna M. McBride; Bruce A. McClane (mBio, 2024)
ABSTRACTSporulation is an important feature of the clostridial life cycle, facilitating survival of these bacteria in harsh environments, contributing to disease transmission for pathogenic species, and sharing common early steps that are also involved in regulating industrially important solvent production by some non-pathogenic species. Initial genomics studies suggested that Clostridia lack the classical phosphorelay that phosphorylates Spo0A and initiates sporulation in Bacillus, leading to the hypothesis that sporulation in Clostridia universally begins when Spo0A is phosphorylated by orphan histidine kinases (OHKs). However, components of the classical Bacillus phosphorelay were recently identified in some Clostridia. Similar Bacillus phosphorelay components have not yet been found in the pathogenic Clostridia or the solventogenic Clostridia of industrial importance. For some of those Clostridia lacking a classical phosphorelay, the involvement of OHKs in sporulation initiation has received support from genetic studies demonstrating the involvement of several apparent OHKs in their sporulation. In addition, several clostridial OHKs directly phosphorylate Spo0A in vitro. Interestingly, there is considerable protein domain diversity among the sporulation-associated OHKs in Clostridia. Further adding to the emergent complexity of sporulation initiation in Clostridia, several candidate OHK phosphotransfer proteins that were OHK candidates were shown to function as phosphatases that reduce sporulation in some Clostridia. The mounting evidence indicates that no single pathway explains sporulation initiation in all Clostridia and supports the need for further study to fully understand the unexpected and biologically fascinating mechanistic diversity of this important process among these medically and industrially important bacteria.